Designing a magic flask: a new activity for teaching nature of science in both formal and informal learning environments. (3rd July 2019) - Eren-Sisman, Ece N.; Koseoglu, Fitnat
Abstract: The magic flask, which is a kind of black box activity, builds an environment for science teachers to discuss nature of science in a formal or/and informal learning environment in the context of the history of science through an explicit-reflective approach. In the activity, the nature of science (NOS) aspects are explicitly addressed and opportunities are provided for high school students to reflect on how these ideas relate to the working principle of the magic flask. This activity could be conducted not only in a science center where the "magic flask" exhibition has introduced but also in a classroom environment where a science teacher presented a video about how the magic flask works. Students, who work a team of three to four, create their own model and test and evaluate it by comparing other models formed by their peers through the engineering design. The Magic flask activity could be assessed through informal questioning and NOS assessment scales. It is a very useful activity since NOS aspects could be discussed explicitly in the formal or informal settings within the history of science while students were actively engaged in an engineering design process.